Enhancing Indonesian students’ literary interpretation through affective stylistics, mood-tone, and cultural contrast - Margaret Stevani; Murad Sawalmeh; Alexander Adrian Saragi; Evi Martiningsih; Rinovian Rais (LingTera, 2026)
This study examined how Indonesian EFL undergraduates interpreted English literature by integrating affective stylistics, mood–tone analysis, and cultural contrast into a unified interpretive framework. Employing a qualitative interpretive case study, data were collected from 24 literature majors in North Sumatra through close-reading tasks, think-aloud protocols, and semi-structured interviews. All instruments underwent expert validation and interrater reliability checks to ensure consistency in affective and tonal coding. Data were analyzed thematically to trace how students’ cognitive-affective responses unfolded during real-time reading. Using selected passages from Harry Potter, The Lord of the Rings, and The Hunger Games, the findings revealed three systematic distortions: affective misalignment, marked by reduced emotional cues; tonal misclassification, where markers of probability were interpreted as certainty; and moral domestication, marked by the simplification of ethical ambiguity into binary judgments. These patterns demonstrated an affective cultural overlay, in which readers unconsciously replaced foreign affective cues with culturally familiar ones. The study underscored the need for pedagogical interventions that foster interpretive flexibility and minimize culturally driven misreadings.